The analysis of competency based for indonesian construction labourers - Fahmi Jaes, Mohd; Isa, Khairunesa; Rahman Ahmad, Abd; Md. Yusoff, Rosman (International Journal of Engineering and Technology, 2018)
Competency is considered a crucial factor for an organisation to compete in a challenging construction environment. From an organisation perspective, it becomes a competitive advantage for a company. For the labourers, it becomes an advantage to compete in getting a job and earning a higher salary. The objective of this study is to identify what are the job specifications of Indonesian construction labourers in terms of KSAo (knowledge, skills, abilities, and other characteristics) elements and to identify competency levels among 300 samples by using questionnaire as an instrument of research. Results showed that most of them are experienced, able to contribute by giving ideas, able to communicate in Malay, as well as competent. However, majority of them do not have a green card, having little to no education background and difficulties in communicating in certain languages. This reflects in their low salary.
Keywords: Competency; Construction Workers; Performance